6-Gingerol attenuates subarachnoid hemorrhage-induced early brain injury via GBP2/PI3K/AKT pathway in the rat model - Tang, Hui; Shao, Chuan; Wang, Xiaoya; Cao, Yi; Li, Zhou; Luo, Xiaoquan; Yang, Xiang; Zhang, Yuekang (Frontiers in Pharmacology, 2022)
Numerous studies have elucidated the neuroprotective effect of 6-gingerol in central nervous system diseases. However, the potential role and mechanism of 6-gingerol on early brain injury (EBI) after subarachnoid hemorrhage (SAH) remains poorly understood. Here, we report that 6-gingerol exerts a neuroprotective effect on SAH-induced EBI through the GBP2/PI3K/AKT pathway. A SAH rat model was established by injecting femoral artery blood into the cisterna magna. 6-gingerol or vehicle was injected intraperitoneally one hour post-SAH induction. We found that the neurological function score and brain edema of SAH rats were significantly improved after 6-gingerol treatment, as well as neuronal apoptosis was attenuated in SAH rats by Nissl staining assay and TUNEL assay. To further explore potential molecular mechanisms associated with 6-gingerol, RNA sequencing was implemented to investigate the differences in transcriptomes between SAH rats with and without 6-gingerol treatment; and found that the expression of guanylate-binding protein 2 (GBP2) evidently was suppressed with 6-gingerol treatment compared to vehicle group. In addition, dual immunofluorescence was also employed to investigate changes in neurons, astrocytes, and microglia after 6-gingerol treatment. The results showed that GBP2 was expressed in neurons but not astrocytes or microglia. Western blotting analysis results demonstrated that the PI3K/AKT pathway was activated in the SAH rats treated with 6-gingerol. Furthermore, recombinant GBP2 protein and LY294002 (PI3K inhibitor) treatment reversed the effects of 6-gingerol treatment in SAH rats. These results indicate that 6-gingerol suppressed the expression of GBP2 to activate the PI3K/AKT pathway, improve neurologic outcomes, reduce brain edema and neuronal apoptosis. In summary, our findings suggest that 6-gingerol could attenuate EBI post-SAH in rats, and 6-gingerol may serve as a novel candidate neuroprotective drug for SAH-induced EBI.